A Guerra Fria e a dissolução dos conceitos público-privado em The Bell Jar e poesia selecionada de Sylvia Plath - Correia, Susana (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2019)
This paper intends to analyze The Bell Jar and a selection of Sylvia Plath’s poetry focusing on the dissolution of the boundaries between the public and the private spheres during the Cold War, due to a new anticommunist containment ideology. In order to do so, I will resort to an analysis of naturally oppressive spaces that expose that dissolution, while also examining some characters. Ultimately, I aim to evince how Plath subverts national conformity and how in The Bell Jar international politics and individual trauma have similar trajectories.